FROM WELFARE TO WELL-BEING: SHAPING DAIRY ANIMAL WELFARE DYNAMICS IN CHANGING AGRO-ECOSYSTEMS - Rupendra Kumar; C.P. Ghosh; Sanjoy Datta; Anand Kumar Yadav (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Animal welfare refers to an animals capacity to navigate its life circumstances and is grounded in the "five freedoms" and ''four principles" of responsible animal care. This multidimensional construct is gaining significance across social, political, ethical, and scientific realms. However, evaluating animal welfare necessitates a consensus on its definition. Notably, dairy welfare has now been integrated into the spectrum of milk quality standards, bolstering consumer confidence in products originating from animals raised and nurtured in adherence to sound farming practices. Given the intertwined relationship between cattle and humans, prioritizing cattle health and mitigating their suffering stands as an imperative. Owing to its intricate nature, quantifying the welfare of dairy cattle is a multifaceted endeavor, relying on a range of direct and indirect metrics. The selection of welfare indicators and evaluation methodologies, therefore, embodies the foundational assumptions underlying diverse interpretations of animal welfare. The criteria should take animal welfare evaluation based on housing, environment, animal health, seasons, feed, management, etc. into consideration. The housing system is one of the most important factors to consider when assessing an animals welfare because it has an impact on the animals well-being and ability to produce.  Assessment frameworks for animal welfare within dairy farms exhibit diversity shaped by the definition of animal welfare and the intended assessment objectives. In this comprehensive review, we undertake an examination of the indicators and evaluation approaches concerning the welfare of dairy cattle,  aiming to illuminate the intricacies of this vital domain.